Towards Deep Learning in Online Courses: A Case Study in Cross-Pollinating Universal Design for Learning and Dialogic Teaching - Qiongli Zhu; Sarfaroz Niyozov (Journal of the Scholarship of Teaching and Learning, 2024)
This article presents a case study of an online course that cross-pollinated Universal Design for Learning (UDL) and dialogic teaching to facilitate deep learning. Conceptualized through the UDL framework, dialogue and dialogic teaching, and deep learning, our analysis employs the methods of design-based research and thematic analysis to unpack the pedagogical cross-pollination in facilitating deep learning in a postgraduate course in a virtual setting. In particular, we examine the course goals, major online compositions, instruction and pedagogies, and assessment. We also explore student learning experiences in approaching deep learning by analyzing their postings in the discussion forums. Findings include multiple pedagogical strategies that fostered deep learning in this online course. This study contributes to the growing literature on online teaching and learning, particularly through cross-pollinating UDL and dialogic teaching to facilitate deep learning in higher education.